2009
DOI: 10.1210/en.2008-1311
|View full text |Cite
|
Sign up to set email alerts
|

Increased Exposure to Estrogens Disturbs Maturation, Steroidogenesis, and Cholesterol Homeostasis via Estrogen Receptor α in Adult Mouse Leydig Cells

Abstract: Deteriorated male reproductive health has been connected to overexposure to estrogens or to imbalanced androgen-estrogen ratio. Transgenic male mice expressing human aromatase (AROM ϩ mice) serve as an apt model for the study of the consequences of an altered androgenestrogen ratio. Our previous studies with AROM ϩ mice showed that low androgen levels together with high estrogen levels result in cryptorchidism and infertility. In the present study, the AROM ϩ mice were shown to have severe abnormalities in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 66 publications
7
58
0
1
Order By: Relevance
“…The expression of Insl3 in MA-10 Leydig cells is similar to what has been reported in primary Leydig cell cultures and in rodents. For instance, Insl3 expression is known to be repressed by estradiol in vivo in mice and rats (Nef et al 2000, Cederroth et al 2007, Strauss et al 2009, Zhou et al 2011) and this repression was also observed in MA-10 Leydig cells ). Insl3 expression is upregulated by androgens in vivo (Zhou et al 2010) as well as in primary Leydig cells and in MA-10 Leydig cells (Laguë & Tremblay 2008).…”
Section: Cell Culture Transfections and Reporter Assaysmentioning
confidence: 94%
“…The expression of Insl3 in MA-10 Leydig cells is similar to what has been reported in primary Leydig cell cultures and in rodents. For instance, Insl3 expression is known to be repressed by estradiol in vivo in mice and rats (Nef et al 2000, Cederroth et al 2007, Strauss et al 2009, Zhou et al 2011) and this repression was also observed in MA-10 Leydig cells ). Insl3 expression is upregulated by androgens in vivo (Zhou et al 2010) as well as in primary Leydig cells and in MA-10 Leydig cells (Laguë & Tremblay 2008).…”
Section: Cell Culture Transfections and Reporter Assaysmentioning
confidence: 94%
“…Several studies also indicated a role for E2 as a paracrine/autocrine factor in the regulation of steroidogenesis in the Leydig cells from rodents (33). A recent study has demonstrated that the chronic imbalance of the androgen-estrogen ratio in the aromatase transgenic animal leads to severe abnormalities in the development, structure, and function of mouse Leydig cells, and these effects seem to be mediated by ESR1 (34).…”
Section: Testismentioning
confidence: 99%
“…Only recently have a few studies of changes in global testicular gene expression after increased exposure to estrogens been reported [46][47][48]. One of these studies [48] involved a 10-day E2 exposure to normal adult rats, and the results may be compared with those of the present study.…”
Section: Estrogen-regulated Genes In Irradiated Rat Testes 829mentioning
confidence: 87%